Generalized Distribution Associated with Quasi-Subordination in Terms of Error Function and Bell Numbers - S. O. Olatunji; Ş. Altinkaya (Jordan Journal of Mathematics and Statistics, 2025)
Generalized distribution is a statistical tools used in geometric function theory in recent time because of its application to real life problems. In this present work, the generalized distribution associated with quasi-subordination in terms of error function and bell numbers were studied. The first few coefficient bounds were obtained which are used to obtain the Fekete-Szeg¨o inequality. Key words and phrases. Univalent function, analytic function, error function, bell-numbers,quasisubordination, distribution series, probability, q-starlike, q-convex. 2000 Mathematics Subject Classification. 30C45